Students and the Sea: Ocean Literacy in Tanjungpinang, Indonesia - Nur Eka Kusuma Hindrasti (Postgraduate, University of Mataram, 2021)
Low levels of 'ocean literacy' has been identified in many countries and can be a barrier for citizens to engage in environmentally responsible behavior even though improving public awareness about the ocean can benefit society and the environment. This study assessed the level of knowledge, attitude, and behavior towards the ocean of students grades 10-11 (ages 15-17) in Tanjungpinang, Indonesia, a region with strong connections with the sea. A survey was used in a public school and a private school, with a total of 200 students participating in a test about ocean knowledge and a survey about ocean attitude and behavior. Many test questions were aligned with the SOLE (The Survey of Ocean Literacy and Experience) based on 'Ocean Literacy Principles' established by the Ocean Literacy Campaign in the United States. Overall, respondents possess a moderate level of knowledge, a highly positive attitude towards the ocean environment, and a moderate level category on behavior. There are significant differences: the level of behavior in terms of class level, the level of knowledge, and attitudes in terms of subject interest. There is no significant difference in knowledge between private and public schools. There is a correlation between attitude and knowledge and also between attitude and behavior